SCHOOL HEALTH PROGRAM AS AN EDUCATIONAL FACILITY IN INCREASING KNOWLEDGE ABOUT DENTAL AND ORAL HEALTH AT BUNGA BANGSA ELEMENTARY SCHOOL - Elizabeth Pranoto, Amelia; Fauziah, Yessy Andriani; Rahardjo, Pambudi; Agustia, Lita; Budi Teguh, Paulus; Santoso, Budi; Sularsih, Sularsih; Prananingrum, Widyasri; Ayu R, Dyah; Tsurayya, Nur; Widowati, Kharinna; Hadinata, Yongki (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Dental and oral health in Indonesia is still a health problem that requires attention. To address dental and oral health problems in Indonesia, particularly in school-age and adult groups, it is necessary to carry out promotive-preventive activities by inviting local universities and business entities that focus on dental and oral health. The most common dental and oral diseases are caries and periodontal disease. One of the strategies of the Ministry of Health of the Republic of Indonesia in reducing the number of dental caries sufferers is by declaring the "Carry Free Indonesia 2030" program. The lack of knowledge and awareness of the Indonesian population regarding dental hygiene and the difficulty of reaching information due to the geographical conditions in several regions in Indonesia which make it impossible to hamper the distribution of education. The Training of Trainer Program targets teachers and parents for 21 days of morning and evening toothbrushes, teaching children and adults about the benefits of good oral hygiene and showing them how to brush their teeth twice a day with fluoride toothpaste. This program aims to provide comprehensive, applicable and sustainable education and knowledge about dental and oral health to school-age children in Indonesia.